Role of the BCL11A/B Homologue Chronophage (Cph) in Locomotor Behaviour of Drosophila melanogaster. - Murthy, S.; Nongthomba, U. (Neuroscience, 2024)
Functioning of the nervous system requires proper formation and specification of neurons as well as accurate connectivity and signalling between them. Locomotor behaviour depends upon these events that occur during neural development, and any aberration in them could result in motor disorders. Transcription factors are believed to be master regulators that control these processes, but very few linked to behaviour have been identified so far. The Drosophila homologue of BCL11A (CTIP1) and BCL11B (CTIP2), Chronophage (Cph), was recently shown to be involved in temporal patterning of neural stem cells but its role in post-mitotic neurons is not known. We show that knockdown of Cph in neurons during development results in animals with locomotor defects at both larval and adult stages. The defects are more severe in adults, with inability to stand, uncoordinated behaviour and complete loss of ability to walk, climb, or fly. These defects are similar to the motor difficulties observed in some patients with mutations in BCL11A and BCL11B. Electrophysiological recordings showed reduced evoked activity and irregular neuronal firing. All Cph-expressing neurons in the ventral nerve cord are glutamatergic. Our results imply that Cph modulates primary locomotor activity through configuration of glutamatergic neurons. Thus, this study ascribes a hitherto unknown role to Cph in locomotor behaviour of Drosophila melanogaster.